2007
DOI: 10.1002/chin.200714191
|View full text |Cite
|
Sign up to set email alerts
|

Antimalarial Activity of Sesquiterpene Lactones from Vernonia cinerea.

Abstract: Terpenes U 0200 Antimalarial Activity of Sesquiterpene Lactones from Vernonia cinerea. -The new sesquiterpene lactones vernolide C (Ia) and D (Ib) and six known analogues are isolated from the dichloromethane fraction of an aqueous extract. -(CHEA, A.; HOUT, S.; LONG, C.; MARCOURT, L.; FAURE, R.; AZAS, N.; ELIAS*, R.; Chem.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
21
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(21 citation statements)
references
References 1 publication
0
21
0
Order By: Relevance
“…One study shows that the administration of V. cinerea can inhibit the elevated proinflammatory cytokine level in the carrageenan-induced paw edema model (Kumar and Kuttan, 2009). Vernolides are major sesquiterpenoids reported in this plant and are considered as the active principle (Kuo et al, 2003;Chea et al, 2006). In the present study, we, for the first time, report the effect of vernolide-A on inducing apoptosis in B16F-10, a highly metastatic melanoma cell.…”
Section: Research Articlementioning
confidence: 83%
“…One study shows that the administration of V. cinerea can inhibit the elevated proinflammatory cytokine level in the carrageenan-induced paw edema model (Kumar and Kuttan, 2009). Vernolides are major sesquiterpenoids reported in this plant and are considered as the active principle (Kuo et al, 2003;Chea et al, 2006). In the present study, we, for the first time, report the effect of vernolide-A on inducing apoptosis in B16F-10, a highly metastatic melanoma cell.…”
Section: Research Articlementioning
confidence: 83%
“…Another study showed a good antiplasmodial activity of vernolide C and D molecules against W2 . This activity could be due to the presence of alkaloids (Bruneton, 1993) and triterpenes in the plant which mentioned by Chea et al (2006). Alkaloids are one of the most important classes of natural products providing drugs since ancient times.…”
Section: Resultsmentioning
confidence: 99%
“…Sequiterpene lactone from Vernonia cinerea (Chea et al, 2006), and the endoperoxide sesquiterpene lactone, artemisinin from A. annua (Klayman, 1985;Hien and White, 1993) are also from the same family. Artemisinin based combinations are among the best-recommended drugs for treatment of resistant Plasmodium parasites (Nosten and White, 2007).…”
Section: Discussionmentioning
confidence: 99%